Analysis of Kunitz inhibitors from plants for comprehensive structural and functional insights - Bendre, Ameya D.; Ramasamy, Sureshkumar; Suresh, C. G. (International Journal of Biological Macromolecules, 2018)
Legume Kunitz type trypsin inhibitor (KTI) family is one of the most versatile families of proteins. A typical KTI features a single peptide folded in beta-trefoil manner, with the molecular weight about 20-22 kDa and two disulphide bonds. The members are known to inhibit a wide range of serpins proteases at the same time many of them possess unique features. Copaifera langsdoiffii Trypsin inhibitor (CTI) has a beta-trefoil fold made up of two non-covalently bound polypeptide chains with only a single disulfide bridge. Delonix regia Trypsin inhibitor (DrTI) has one amino acid insertion between P1 and P2 of the reactive site distorting its conformation. Bauhinia bauhinioides Cruzipain inhibitor (BbCI) has a conservative beta-trefoil fold but lacks disulfide bonds. Such subtle differences in structures make Kunitz inhibitors different from other inhibitor families. Most of the studies on these inhibitors are focused towards their proposed role in defense from insect pests and wounding but their exact physiological role in nature is still uncharted. Thus, it would be very interesting to closely analyze the structural details of these inhibitors in order to ascertain their biological role and other fascinating applications. (C) 2018 Elsevier B.V. All rights reserved.